Visceral-to-Subcutaneous Abdominal Fat Ratio Is Associated with Nonalcoholic Fatty Liver Disease and Liver Fibrosis - Jung, Chan-Hee (Endocrinol Metab (Seoul), 2020)
BACKGROUND: We evaluated the association of visceral-to-subcutaneous fat ratio (VSR) with nonalcoholic fatty liver disease (NAFLD) and advanced fibrosis degree based on noninvasive serum fibrosis markers in the general population with NAFLD. METHODS: This is a cross-sectional study, in 7,465 Korean adults who underwent health screening examinations. NAFLD was defined as fatty liver detected on ultrasonography, and visceral and subcutaneous abdominal fat was measured using computed tomography. We predicted fibrosis based on the fibrosis-4 (FIB-4) score and aspartate aminotransferase-to-platelet ratio index (APRI) and categorized the risk for advanced fibrosis as low, indeterminate, or high. RESULTS: The multivariable-adjusted prevalence ratios for indeterminate to high risk of advanced fibrosis based on FIB-4, determined by comparing the second, third, and fourth quartiles with the first quartile of VSR, were 3.38 (95% confidence interval [CI], 0.64 to 17.97), 9.41 (95% CI, 1.97 to 45.01), and 19.34 (95% CI, 4.06 to 92.18), respectively. The multivariable-adjusted prevalence ratios for intermediate to high degree of fibrosis according to APRI also increased across VSR quartiles (5.04 [95% CI, 2.65 to 9.59], 7.51 [95% CI, 3.91 to 14.42], and 19.55 [95% CI, 9.97 to 38.34], respectively). High VSR was more strongly associated with the prevalence of NAFLD in nonobese subjects than in obese subjects, and the associations between VSR and intermediate to high probability of advanced fibrosis in NAFLD were stronger in obese subjects than in nonobese subjects. CONCLUSION: High VSR values predicted increased NAFLD risk and advanced fibrosis risk with NAFLD, and the predictive value of VSR for indeterminate to high risk of advanced fibrosis was higher in obese subjects than in nonobese subjects.